The Effect of Perceived Organizational Support and Work Environment on Performance: The Mediating Role of Job Satisfaction at BKN Regional VIII - Wardani, Dwi Magrita Kusuma; Anisah, Hastin Umi (Yayasan Sinergi Kawula Muda, 2026)
This research proposes an integrated mediation framework that investigates how perceived organizational support (POS) and the work environment influence employee performance through the mechanism of job satisfaction at the Regional Office VIII of Indonesia’s National Civil Service Agency. The study responds to a persistent gap in public-sector performance research by linking structural conditions of work with an attitudinal pathway within the Indonesian civil service. A quantitative census involving 86 civil servants was conducted, and the data were processed using PLS-SEM in SmartPLS 4.0. The analysis reveals that both POS and the work environment significantly elevate job satisfaction, although neither factor directly drives performance. Job satisfaction functions as a full mediator for the effects of POS and the work environment on performance and significantly boosts employee performance. The model demonstrates strong explanatory capacity, with R² values of 0.851 for job satisfaction and 0.599 for performance. These results highlight job satisfaction as the principal channel through which supportive practices and conducive work conditions translate into performance. The study strengthens social exchange theory and enriches public-sector HRM literature by showing that, in bureaucratic institutions, performance outcomes stem primarily from employees’ attitudinal responses to organizational support and work quality.